High Voltage Stable Li Metal Batteries Enabled by Ether-Based Highly Concentrated Electrolytes at Elevated Temperatures. Issue 11 (21st July 2020) - Leng, Yongjun; Ge, Shanhai; Longchamps, Ryan S.; Yang, Xiao-Guang; Liu, Teng; Wang, Chao-Yang
Abstract : Li metal batteries (LMBs) employing high voltage cathodes are necessary to attain high energy density. Although highly concentrated ether-based electrolytes (e.g. 4 M LiFSI/DME) can yield stable cycling of Li metal anodes, their high voltage instability fosters incompatibility with high voltage cathodes. In this work, the temperature dependence of fresh cell performance, Li Coulombic efficiency (CE), and cycling stability of LMBs in highly concentrated LiFSI/DME electrolytes was explored. Elevated temperature operation was deemed essential for highly concentrated electrolytes to achieve practical rate capability. Moreover, at 60 °C, the cycling stability of Li metal anodes with a Li CE as high as 99.2% was demonstrated in a highly concentrated LiFSI-1.2DME electrolyte (LiFSI: DME = 1: 1.2 mol.). At room temperature, the LiFSI-1.2DME electrolyte enabled stable LMBs with NMC622 cathodes. However, due to the high temperature and high voltage instability of the LiFSI-1.2DME electrolyte in contact with NCM622, a small amount of TAP (∼1 wt.%) was added, significantly enhancing the cycling stability at 60 °C. This newly developed LiFSI-1.2DME electrolyte with 1 wt.% TAP ultimately enabled LMBs with NMC622 cathodes and minimal excess Li metal anode to be cycled stably for 200–300 cycles at 60 °C.